Two-stage treatment with hepatectomy and carbon-ion radiotherapy for multiple hepatic epithelioid hemangioendotheliomas - Komatsu, Shohei (Baishideng Publishing Group Inc, 2014)
Hepatic epithelioid hemangioendothelioma (HEH) is a rare neoplasm of vascular origin with variable malignant potential. Because most patients with this condition have multiple bilobar lesions, liver transplantation is the standard treatment, and hepatectomy is much less frequently indicated. We describe a case of a 35-year-old woman with unresectable multiple bilobar HEH successfully treated by combination treatment with hepatectomy and carbon-ion radiotherapy. This case is very meaningful since it demonstrated the effectiveness of carbon-ion radiotherapy for HEH and the possibility of expanding the curative treatment options for multiple bilobar hepatic tumors.